A Traveling Mission: Albert E. Kahn in the USSR - Olga Yu. Panova (Литература двух Америк, 2025)
The paper is devoted to an episode of Soviet-American cultural and literary relations at the turn of the 1950s–1960s, connected with American writer and journalist Albert Eugene Kahn (1912–1979). The article reconstructs the history of his Soviet travels and his joint projects with the USSR. Almost forgotten in contemporary Russia, he was very popular in the Soviet Union in the first two postwar decades. Kahn became famous in the 1940s and early 1950s as an investigative journalist. In 1958–1960 he regularly visited the USSR, where all his major books were translated and published. He maintained extensive contacts with the Soviet Writers’ Union, many Soviet cultural institutions, publishing houses, newspapers and magazines, often published articles in the Soviet press and gave lectures. His famous book Days with Ulanova (1962; Russian edition 1963) was prepared in close cooperation with the Soviet side. Kahn, carrying on the traditions of his family, tried to strengthen Soviet-American cultural links, seeing it as an important tool in the struggle for peace. It is noteworthy that the documents stored in the archive of the Soviet Writers’ Union reveal a striking contradiction between his private and public behavior: Soviet translators, journalists and functionaries complained in their reports about his intolerable character and sarcastic criticism aimed at the shortcomings of the Soviet system and especially the institutions receiving foreign visitors. At the same time, when speaking in public as well as in his writings Kahn was a committed apologist and staunch propagandist of the Soviet regime and its achievements. The article attempts to explain this paradox. Kahn’s correspondence with the Foreign Commission of the Soviet Writers’ Union from the Russian State Archive of Literature and Art is published in the Addendum.